Implementasi Nilai Ketuhanan Dalam Pembentukan Karakter Siswa Kelas II SDS Pengharapan Sejati GBI Efata Sampali - Hanna Olyvia Manurung; Geby Juwita Patrisia Butar-buta; Renni Lumban gaol; Selviona Dara Perbina; Irma Ida Sihombing; Ahmad Nando Telaumbanua (CV. ITTC INDONESIA, 2025)
This research investigates how the value of divinity is applied in education at Efata Sampali SDS Pengharapan Sejati GBI and how it impacts on student character building. This research uses a descriptive qualitative approach involving data analysis based on literature study. The results show that the value of Godhead can be applied through joint prayers, regular worship, and religious teaching that instills moral values such as honesty and empathy. However, the influence of technology that distracts students and the lack of deep spiritual understanding are some of the problems when using it. The results show that applying God's value improves students' character, especially in terms of discipline, responsibility, and concern for others. Having said that, there are still barriers to improving a deeper understanding of spiritual principles. This is mainly due to the lack of parental involvement and religious differences among students. Therefore, utilizing technology and a more inclusive approach can help improve the effectiveness of learning. In summary, the application of God's values in primary schools is helpful in the character building of students. To achieve better results, teachers, parents and society should work together to provide more in-depth character education. In addition, students can gain a better understanding of God's principles in daily life by using innovative and technology-based educational approaches.